2018
DOI: 10.1002/14651858.cd011537.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine administration of human chorionic gonadotropin (hCG) for subfertile women undergoing assisted reproduction

Abstract: Newcastle University ePrints-eprint.ncl.ac.uk Craciunas L, Tsampras N, Coomarasamy A, Raine-Fenning N. Intrauterine administration of human chorionic gonadotropin (hCG) for subfertile women undergoing assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 46 publications
(6 reference statements)
2
29
0
Order By: Relevance
“…19,20 Intriguingly, hCG promotes uterine NK cell proliferation through mannose receptors but not through LH/ CG-R because NK cells do not express LH/CG-R. [23][24][25] However, there is no consensus regarding the level of efficacy or the most responsive patient populations to this treatment. A clinical trial has suggested that intrauterine administration of autologous peripheral blood mononuclear cells (PBMCs) activated by hCG increases the implantation and pregnancy rates in patients with repeated implantation failure.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Intriguingly, hCG promotes uterine NK cell proliferation through mannose receptors but not through LH/ CG-R because NK cells do not express LH/CG-R. [23][24][25] However, there is no consensus regarding the level of efficacy or the most responsive patient populations to this treatment. A clinical trial has suggested that intrauterine administration of autologous peripheral blood mononuclear cells (PBMCs) activated by hCG increases the implantation and pregnancy rates in patients with repeated implantation failure.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in recent years have investigated the impact of this intrauterine hCG administration before embryo transfer in patients with repeated implantation failures. The results of these studies are controversial (153)(154)(155). The differences in design and population can explain the contradictory results.…”
Section: Infusion Of Hcg During Embryo Transfermentioning
confidence: 99%
“…In a recent Cochrane review from Craciunas et al (45), it is proposed that in particular patients undergoing cleavage-stage embryo transfer receiving an hCG dosage above 500 IU benefit from intrauterine hCG injection but not patients undergoing blastocyst transfer. The last meta-analysis from 2019 concluded that intrauterine hCG administration before embryo transfer could significantly improve IR, CPR, OPR, and LBR and significantly lowered the MR.…”
Section: Clinical Application Of Hcg In Artificial Reproductive Technmentioning
confidence: 99%